Quality Control Design to Reduce Shoes Production Defects Using Root Cause Analysis and Lean Six Sigma Methods - A Faisal Burhanuddin; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2022)
PT. Kharisma S.F is a company that produces sporty shoes with the Eagle, Nevada, and Fladeo brands. PT. Kharisma experienced a defect in the production process, which occurred in the sewing process and assembly process. However, the most common disability experienced by PT. S.F's charisma is a defect in the sewing process. This research focuses on the inspection of the production of Eagle brand shoes. With these problems, it is necessary to carry out quality control, which is useful for regulating the various products produced so that they can have good quality. To determine the level of a defect in the DPMO value and sigma value, to find out the various factors that cause the high level of product defects, and to provide suggestions for improvement and quality control to reduce the number of product defects, Root Cause Analysis (RCA) and Lean Six Sigma methods were used. Data were obtained from the company for three months and from 6 respondents to identify waste. From the results of research conducted. It can be seen that the factor that most influences the length of waiting time in production is the human factor. The highest identification of waste is defects. There are two types of defects, namely sewing defects and assembly defects. As for alternative improvements to reduce the number of defects, namely checking machine parts on the production floor with a checklist every day and replacing machine parts that are damaged or have expired, and providing regular training to operators scheduled once every three months.